Pengaruh Latihan Fleksibilitas Statis Terhadap Kekakuan Lutut Lansia - Sumarni , Yasinta Lidia; Putri, Rona Sari Mahaji; Devi, Hilda Mazarina (Jurnal Surya, 2025)
Introduction: Knee joint stiffness is a common musculoskeletal problem among older adults. Age-related physiological changes lead to a decline in physical function and mobility, resulting in a reduced range of motion in the joints. This study aimed to compare knee joint stiffness before and after the implementation of static flexibility training in older adults. Methods: This quantitative experimental study employed a one group pretest–posttest design. A total of 18 older adults experiencing knee joint stiffness at Betheseda Kasih Service Nursing Home were recruited using simple random sampling. Knee joint stiffness was measured using a goniometer and an observation sheet. Data were analyzed using the Wilcoxon signed-rank test. Static flexibility training was conducted six times over a two-week period (three sessions per week), with each session lasting approximately 15 minutes. Each session consisted of five movements performed for 10–20 repetitions. Results: Prior to the intervention, the mean degree of knee joint stiffness was 75° (classified as stiff). Following the static flexibility training, the mean degree decreased to 48.89°, indicating a return to normal joint mobility. The Wilcoxon test showed a statistically significant effect of static flexibility training on reducing knee joint stiffness (p = .000 < 0.001). Conclusion: Static flexibility training effective for improving joint mobility in older adults as a non-pharmacological approach. It is recommended to compare static and dynamic flexibility training effectiveness reducing knee joint stiffness among older adults in further study.